PENGELOLAAN PEMBELAJARAN SEBAGAI UPAYA UNTUK MENINGKATKAN LAYANAN PENDIDIKAN BAGI ANAK PUTUS SEKOLAH PADA KOMUNITAS DINDING MANADO - Kalintabu, Heliyanti; Palar, Yolanda Nany (Peneliti.net, 2024)
Learning management is a crucial strategy for enhancing educational services, particularly for out-of-school children. This study focuses on the Dinding community in Manado, which faces significant challenges in accessing education. The objective of this research is to analyze the learning management strategies that can be implemented in the non-formal education setting of the Dinding community. The research employs a qualitative methodology utilizing interviews and observations. The findings indicate that, although the Dinding community serves as a non-formal educational platform, learning management and classroom management are not markedly different from those in formal education. Each learning session concludes with an evaluation to assess the achievement of learning objectives, identify challenges faced, and collaboratively discuss potential solutions. Evaluations are conducted with the involvement of the teaching staff present at the time. The conclusion emphasizes the importance of adaptive and collaborative learning management as a strategic effort to provide better educational services for children in underserved communities. Recommendations are intended to offer insights for policymakers in designing inclusive and sustainable educational programs.